2014
DOI: 10.1016/j.virol.2013.12.020
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-23 inhibits PRRSV replication by directly targeting PRRSV RNA and possibly by upregulating type I interferons

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression post-transcriptionally and play critical roles in intricate networks of host-pathogen interactions and innate immunity. Porcine reproductive and respiratory syndrome (PRRS) is one of the most important diseases affecting swine industry worldwide. Here, we demonstrated that miR-23, miR-378, and miR-505 were antiviral host factors against PRRS virus (PRRSV). Over-expression of the three miRNAs inhibited PRRSV infection in a dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 42 publications
3
66
0
2
Order By: Relevance
“…Previous studies have shown that some miRNAs, such as miR-125b (21), miR-26a (22), and miR-23 (42), could inhibit the replication of PRRSV, while miR-24-3p (23), upregulated by PRRSV infection in MARC-145 cells, and ssc-miR-30d-R_1 (18), downregulated by PRRSV infection in pig lungs, could promote virus replication. Notwithstanding these reports, we found that PRRSV infection upregulated the expression of (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that some miRNAs, such as miR-125b (21), miR-26a (22), and miR-23 (42), could inhibit the replication of PRRSV, while miR-24-3p (23), upregulated by PRRSV infection in MARC-145 cells, and ssc-miR-30d-R_1 (18), downregulated by PRRSV infection in pig lungs, could promote virus replication. Notwithstanding these reports, we found that PRRSV infection upregulated the expression of (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cotransfection of small RNAs with DNA constructs was conducted using Lipofectamine 2000 reagent (Invitrogen), according to the manufacturer's instructions. For quantitative real-time PCR (qRT-PCR) analysis of mRNA or miRNA expression, total RNAs were extracted, reverse transcribed, and amplified, as described previously (35). For miRNA analysis, the reverse transcription primer for miR-30 was 59-GCGAGCACAGAATTAATACG-ACTCACTATAGGTTTTTTTTTTTTVN-39.…”
Section: Transfection and Quantitative Real-time Pcrmentioning
confidence: 99%
“…The relative expression levels of miRNAs were normalized to U6. Previously described primers were used for mRNA analysis of porcine MX1, ISG15, PRRSV ORF7, and GAPDH (35,36). Other specific primers for qRT-PCR analysis are listed in Table II.…”
Section: Transfection and Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence indicates that miRNAs can participate in the regulation of almost every cellular activity and their abnormal expression is associated with many human diseases. Recently, several studies have demonstrated that miRNAs can regulate PRRSV infection and replication [5][6][7][8]. Here we discuss the current understanding of the role of miRNA in PRRSV infection and hypothesize that cellular miRNAs may contribute significantly to regulating PRRSV infection.…”
Section: Introductionmentioning
confidence: 90%